FRI0166 Characterisation of phosphodiesterase 4 (PDE4) blockade in the synovium of psoriatic arthritis patients: a focus on synovial invasiveness and t-cell polyfunctionality. (12th June 2018) - Wade, S.M.; Canavan, M.; McGarry, T.; Wade, S.C.; Veale, D.J.; Fearon, U.
Abstract : Background: Owing to the multi-faceted nature of the pathogenesis of psoriatic arthritis (PsA), the development of multi-targeted agents has been an area of intensive research. Such agents include the phosphodiesterase 4 (PDE4) inhibitors, Rolipram and Apremilast, which elevate intracellular cAMP levels to modulate a number of anti-inflammatory mechanisms. However, the effect of PDE4 blockade within the complex inflammatory environment of the inflamed synovium remains to be elucidated. Objectives: To characterise the effect of PDE4 blockade in PsA using ex vivo synovial whole tissue explants and synovial single cell suspensions reflective of the complex synovial micro-environment. Methods: Ex-vivo PsA whole tissue synovial explants were cultured in the presence of PDE4 inhibitor, Rolipram, for 24 hour. The expression of pro-inflammatory mediators were quantified by ELISA and MSD multiplex. A 21 day synovial explant matrigel model was utilised to examine synovial fibroblast (SFC) invasiveness to allow for a long-term assessment. For the characterisation of synovial T-cells, synovial explants were digested and cultured in the presence of Rolipram for 8 hours, stimulated and stained for surface and intracellular T-cell markers. Cell surface expression of CD161 was used to identify Th17 lineage (CD161 +Th17 and exTh17 cells) or non-Th17 lineage (CD161-) Th1 cells. SPICE analysis was utilised to determine the proportions of mono- and polyfunctional T-cells, which were correlated with disease activity scores. Results: Rolipram treatment inhibited the spontaneous secretion of inflammatory mediators IL-6, IL-8, MCP-1 and MMP-1 (all p<0.05), with a parallel increase in IL-10 expression. Under DMSO control conditions, a significant increase in SFC outgrowths from PsA explants (indicative of SFC invasiveness) was observed from day 8–21 (all p<0.05), effects of which were significantly decreased in the presence of Rolipram (all p<0.05). A comparative analysis of T cells in PsA PBMC and synovial tissue revealed an enrichment of Th1 (p<0.05), Th17 (p=0.06) and exTh17 (p<0.05) cells in PsA synovial tissue, which displayed distinct polyfunctional cytokine profiles, in particular Th17 cells, as compared to matched PBMC. The frequency of polyfunctional triple positive GM-CSF/TNF/IL-17 and or IFNy producing Th1 (r=0.8, p<0.05), Th17 (r=0.6, p<0.16) and exTh17 (r=0.9, p<0.05) cells positively correlated with PsA disease activity, suggesting an important role of T-cell polyfunctionality in PsA synovial pathogenesis. Analysis of synovial tissue cell suspensions and matched PBMC cultured in the presence of Rolipram showed a significant decrease in the proportion of these triple positivesynovial T cells compared to DMSO (p<0.05), suggesting that PDE4 blockade can effectively targets the polyfunctional hyper-pathogenic synovial T cells in PsA, particularly polyfunctional CD8 +T cells and Th17 lineage, Th17 and exTh17 cells. Conclusions: PDE4 blockade mediates broad anti-inflammatory mechanisms in PsA synovial tissue through the reduced expression of pro-inflammatory mediators, decreased invasiveness and reduced T cell polyfunctionality. We also demonstrate the feasibility of using ex vivo models to determine " in situ like" assessments of therapeutic agents and further our understanding of disease pathogenesis. Disclosure of Interest: None declared